Pemberdayaan Komunitas Pengungsi Melalui Program Dukungan Psikososial Terintegrasi Berbasis Mobil Layanan Anak Di Kota Medan - Balqis Nurmauli Damanik; Surya Utama; Hely; Syahferi Anwar; Tifani Hadi Tri Wahyuni; Achmad Huzairy Manurung; Ledi Isni Br. Pasaribu (STIKES Columbia Asia Medan, 2025)
The floods that struck Medan City between late November and early December 2025 significantly affected the psychosocial wellbeing of children aged 4–7 years living in evacuation shelters. Children in this developmental stage are highly vulnerable to stress, anxiety, and behavioral changes following disaster exposure. This community service program aimed to implement an Integrated Psychosocial Support Model designed to promote emotional recovery among children and strengthen the capacities of parents and shelter facilitators. The methods included play-based psychosocial activities, safe digital literacy education, parental engagement sessions, and capacity-building for local volunteers. The intervention was conducted at two evacuation shelters in Medan Labuhan and Belawan, involving approximately 220 children. The results demonstrated substantial improvements in adaptive behavior indicators—group participation, ability to follow instructions, positive emotional expression, and peer interaction—with an average increase of 1.25 points. Social transformations also emerged, including the establishment of child-friendly spaces, enhanced supportive parenting practices, and the rise of local leaders within the community. These findings indicate that integrated psychosocial support is an effective approach for post-disaster child recovery and can be replicated in similar humanitarian settings.